2021
DOI: 10.1021/acs.jafc.1c01712
|View full text |Cite
|
Sign up to set email alerts
|

Peptides Released from Extruded Adzuki Bean Protein through Simulated Gastrointestinal Digestion Exhibit Anti-inflammatory Activity

Abstract: Increasing attention has been focused on plant-derived peptides because of their potential bioactivities. In this study, bioactive peptides were released from extruded adzuki bean protein by simulated gastrointestinal digestion. A peptide (KQS-1) sequenced as KQSESHFVDAQPEQQQR was separated and identified using ultrafiltration, pre-high-performance liquid chromatography (HPLC), and ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). KQS-1 was shown to exert significant anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…For example anti-inflammatory peptides VPP and IPP resulting from bacterial fermentation of milk, IRW and IQW obtained from egg casein, and PAY isolated from salmon byproduct protein, and PTGADY from Alaska pollock protein [10] have molecular weight less than 1 kDa [26]. The exact relationship between peptide size and its anti-inflammatory activity is not well-established, but some reports attributed the higher anti-inflammatory of small-sized peptides to the easier absorbance by immune cells [12]. Peptides that penetrate cells usually have a sequence length of 5 to 42 amino acids [27].…”
Section: Immunomodulatory Activity Of Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example anti-inflammatory peptides VPP and IPP resulting from bacterial fermentation of milk, IRW and IQW obtained from egg casein, and PAY isolated from salmon byproduct protein, and PTGADY from Alaska pollock protein [10] have molecular weight less than 1 kDa [26]. The exact relationship between peptide size and its anti-inflammatory activity is not well-established, but some reports attributed the higher anti-inflammatory of small-sized peptides to the easier absorbance by immune cells [12]. Peptides that penetrate cells usually have a sequence length of 5 to 42 amino acids [27].…”
Section: Immunomodulatory Activity Of Peptidesmentioning
confidence: 99%
“…Although it is well-established that the biological activities of peptides depend on their molecular weight and amino acid sequences, the link between the structure and function is not fully understood [5]. Small peptides below 1 KDa derived from different sources such as IPP and VPP from fermented milk [5], IRW and IQW from egg protein [6,7], PLV and VPY from soy protein [8,9], PTGADY from Alaska pollock protein [10], and PAY from salmon protein [11] can be absorbed by immune and skin cells and modulate cell functions [12]. In these peptides, hydrophobic amino acids are the key players in their anti-inflammatory activity and proliferative properties on fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Adzuki bean dietary fiber reduced visceral fat accumulation in rats fed a normal diet ( 15 ). The biologically active peptides in adzuki bean exhibited significant anti-inflammatory activity by inhibiting the expression of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) ( 16 ). In addition, adzuki bean water extract containing polyphenols attenuated obesity by regulating gut microbiota ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that inflammation is associated with many chronic diseases such as cancer, obesity, and gastrointestinal diseases. Fortunately, several food components, such as proteins [ 16 ], polysaccharides [ 17 ], and polyphenols, [ 18 ] are proven to have an ability to antagonize the induced inflammation. It was found that mung bean protein hydrolysates [ 19 ], sturgeon protein-derived peptides [ 20 ], and sea buckthorn flavonoids [ 21 ] were able to regulate the expression of inflammatory markers in the LPS-stimulated RAW 264.7 macrophages and then activate the relevant signaling pathways to exert an anti-inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%